2022
DOI: 10.5812/jjcmb.121808
|View full text |Cite
|
Sign up to set email alerts
|

Region Specificity in Endogenous Opioid Peptides and Mu-opioid Receptor Gene Expression in Rat Brain Areas Involved in Addiction After Frequent Morphine Treatment

Abstract: Backgrounds: Molecular mechanisms involved in adverse effects of morphine, including tolerance and dependence, have remained elusive. We examined possible alterations in the gene expression of proenkephalin (Penk), prodynorphin (Pdyn), and mu-opioid receptor (Oprm1) in reward brain areas following frequent morphine treatment. Methods: Two groups of male Wistar rats were used. The groups received either saline (1 mL/kg) or morphine (10 mg/kg) twice daily for eight days. On day 8, rats were decapitated, brain ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
1
1
Order By: Relevance
“…It has been shown that long-term administration of morphine induces desensitization and/or endocytosis of MORs to attenuate input signaling to the cell (40). However, the increased Oprm1 mRNA due to frequent morphine exposure in the present study may indicate a compensatory mechanism in response to the possible decreases in MORs in the ventral striatum (41). Further, accumulating evidence also shows that morphine, via binding to TLR4, increases pro-inflammatory cytokines, which partly mediate opioid tolerance and dependence (6,42).…”
Section: Discussioncontrasting
confidence: 55%
“…It has been shown that long-term administration of morphine induces desensitization and/or endocytosis of MORs to attenuate input signaling to the cell (40). However, the increased Oprm1 mRNA due to frequent morphine exposure in the present study may indicate a compensatory mechanism in response to the possible decreases in MORs in the ventral striatum (41). Further, accumulating evidence also shows that morphine, via binding to TLR4, increases pro-inflammatory cytokines, which partly mediate opioid tolerance and dependence (6,42).…”
Section: Discussioncontrasting
confidence: 55%
“…The analgesic effects of morphine were partly restored 30 days post-withdrawal, though not to the levels seen on the first day of administration. Chronic morphine use alters molecular and cellular pathways, especially in brain regions involved in reward and pain processing (23)(24)(25), thus changing the brain's response to the drug (26). Prior research has shown that an eight-day regimen of morphine injections induces tolerance and dependence (26).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic morphine use alters molecular and cellular pathways, especially in brain regions involved in reward and pain processing (23)(24)(25), thus changing the brain's response to the drug (26). Prior research has shown that an eight-day regimen of morphine injections induces tolerance and dependence (26). Frequent morphine use reduces its therapeutic effects and increases addiction risk (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the current study and shown to decrease both sucrose consumption and motivated behavior in opioid-naïve animals 48,49 . Chronic opioid exposure has been associated with decreases in opioid receptor expression and availability as well as decreased endogenous opioid peptide gene expression in the VTA [50][51][52] . And while heroin IVSA in rodents does not seem to change mu opioid receptor expression in either sex 53 , protracted heroin withdrawal in male mice results in increased proopiomelanocortin (precursor to endogenous opioid production) cell reporter signal and mRNA levels in the amygdala and hippocampus, respectively 51 .…”
Section: Discussionmentioning
confidence: 99%